Pulmonary function and respiratory muscle strength in myasthenia gravis. - Oliveira, Ezequiel Fernandes; Nacif, Sergio Roberto; Fonseca, Nina Teixeira; Apostólico, Nadua; Urbano, Jessica Julioti; Guimarães, Letícia Lopes; Perez, Eduardo de Araujo; Cavalcante, Valéria; Bulle, Acary Sousa; Oliveira, Luis Vicente Franco (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Myasthenia gravis (MG) is a neuromuscular autoimmune disease of unknown etiology, characterized by generalized muscle weakness and fatigue, especially after repetitive physical activities, with consequent improvement after rest. The MG follows a slowly progressive course, which can be fatal failure of the ventilatory muscles. The manifestations of the respiratory system are generally attributed to the weakness of the diaphragm and also accessory muscles of ventilation. Objetive: The objective was to evaluate the volumes and lung capacities and maximum pressure ventilation in patients with clinically stable MG. Methods: This is an observational study involving 15 patients (2 men) with MG. Subjects were recruited consecutively and screened for eligibility using the standardized protocol. Results: Spirometry, only two patients showed abnormalities of respiratory pattern, being a moderate restrictive pattern (50-60% predicted), and another patient with the congenital form showed a severe restrictive pattern. Not obstructive patterns were observed. Our results of spirometry showed an average value of FVC: 3.15 ± 0.77 and FEV1: 2.64 ± 0.65. Regarding the maximum pressure generated by the ventilatory muscles, the average value for the MIP was 45.5 cmH2O among women and the value of 56 cmH2O for men was observed. To MEP it was observed the average value of 45 cmH2O for women and 55 cmH2O for men. Conclusion: We conclude that patients with MG have lower values of maximal inspiratory and expiratory ventilatory associated with normal lung function values.